2021
DOI: 10.1002/cam4.4224
|View full text |Cite
|
Sign up to set email alerts
|

Identification of colon tumor marker NKD1 via integrated bioinformatics analysis and experimental validation

Abstract: Background Colorectal cancer is an important death‐related disease in the worldwide. However, specific colon cancer tumor markers currently used for diagnosis and treatment are few. The purpose of this study is to screen the potential colon cancer markers by bioinformatics and verify the results with experiments. Methods Gene expression data were downloaded from two different databases: TCGA database and GEO datasets, which were then analyzed by two different methods (difference analysis and WGCNA method). Ven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 31 publications
0
17
2
Order By: Relevance
“…GAPDH and U6 were used as internal controls for mRNA and miRNA, respectively. 5 The primer sequences are shown in Table S2 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…GAPDH and U6 were used as internal controls for mRNA and miRNA, respectively. 5 The primer sequences are shown in Table S2 .…”
Section: Methodsmentioning
confidence: 99%
“…Our previous study demonstrated that NKD1 could promote colon cancer cell proliferation. 5 The molecular mechanism by which NKD1 regulates colon cancer progression remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…All cells were cultured at 37 °C in a humidifed atmosphere containing 5% CO2. Cells were transiently transfected with pcDNA3-NKD1 plasmids (YSY Biotech, Nanjing, China) using pcDNA3-vector as negative control [18] by Lipo3000 reagent (Termo Fisher Scientifcs, Pittsburgh, USA).…”
Section: Cell Culture and Transfectionmentioning
confidence: 99%
“…Furthermore, NKD1 was elevated in specifc mouse models of intestinal tumors comparing to healthy tissues, which represents a biomarker of tumor growth [17]. Moreover, NKD1 is highly expressed in colon carcinomas and enhances colon cancer growth according to both bioinformatics analyses and experimental validations [18].…”
Section: Introductionmentioning
confidence: 99%
“…Washah et al ( 6 ) analyzed the principle and prospects of bioinformatics tools and databases in detail and concluded that they offer significant advantages and have broad prospects in the treatment of cancer. Relevant predictions indicate that CCNB1, CCNA2, COL1A1, and COL1A2 (extracted by bioinformatics screening) play a key role in malignant progression and the prognosis of hepatocellular carcinoma and colon cancer ( 7 , 8 ).…”
Section: Introductionmentioning
confidence: 99%